Answered

Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Simplify. –7 + 2(x – 3)

A. x - 10
B. x - 13
C. 2x - 10
D. 2x - 13


Sagot :

[tex]-7 + 2(x -3) =-7+2x-6=2x-13[/tex]
[tex]-7+2(x-3)\\use\ distributive\ property:a(b+c)=ab+ac\\\\-7+2(x)+2(-3)=-7+2x-6\\use\ commutative\ property:a+b=b+a\\\\2x+(-7)+(-6)=\boxed{2x-13}\to\boxed{D}[/tex]